Evaluation of various water quality indices for monitoring of water quality of Sg. Sarawak - Nurzawani, Binti Md. Sofwan (Universiti Malaysia Sarawak (UNIMAS), 2013)
Water quality is a term used to describe the chemical, physical and biological characteristics of water in respect to its suitability for a particular purpose and related with a set of standards. The knowledge of water quality and its content are essential to track any influx of water pollutants that are detrimental to human and ecosystem. The study aimed to examine the water quality status of Sg. Sarawak particularly in Waterfront and Satok Bridge based on three water quality monitoring approaches namely Water Quality Index (WQI), average NWQS and the extended NWQS (eNWQS,9 The eNWQS was designated using Partial Least Square (PLS) regression where multivariate water quality data is directly correlated to the classes according to NWQS. Generally, the average NWQS and eNWQS corresponded well with the WQI in determining the river water quality status. The river water quality for both sampling points was categorized as slightly polluted with the index ranged from 62 to 68. In terms of sensitivity, the average NWQS approach was less sensitive because it interpreted the class which the value of each parameter fell within it without took into account the absolute value of the parameter. The eNWQS shows sensitivity but further study is required to verify the sensitivity level between eNWQS and WQI. This study emphasizes that the eNWQS constitutes of useful and practical approach. The study results should therefore encourage water quality monitoring authorities and water resources managers to adopt eNWQS model as a feasible option in determining water quality status in Malaysia.